Evaluate Sustainable FDI to Promote Sustainable Development - John M. Kline (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Prescriptions to increase the role of FDI in promoting sustainable development generally focus on the macro level – getting policies right and otherwise improving the investment climate. These steps are necessary but not sufficient. Effective implementation processes, especially at the micro project level, are also essential to encourage FDI that matches host country development needs and priorities.
Keywords: 330